Pengaruh Audit Internal dan Efektivitas Pengendalian Internal Terhadap Deteksi Kecurangan (Fraud) Pada PT. BPR Agro Cipta Adiguna - Hafizna, Nidiva (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This study aims to examine the influence of internal audit and the effectiveness of internal control on fraud detection at PT. BPR Agro Cipta Adiguna. Data collection was conducted using a quantitative method with questionnaires distributed to 30 respondents working at the company. Data analysis was performed using multiple linear regression to test the proposed hypotheses. The results show that both internal audit and the effectiveness of internal control have a significant effect on fraud detection. These findings emphasize the importance of an effective internal control system and internal audit role in preventing fraud within organizations. This research contributes to understanding the relationship between internal audit, internal control, and fraud detection in the banking sector.